Braconidae aus den Resten der Ratzeburg-Sammlung (Hymenoptera). - Königsmann, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The greatest part of the Ratzeburg collection was destroyed towards the end of World War II. The part which outlived the war is dealt with in this paper. A total of 65 species is studied here 61 of which were described by Ratzeburg . The types of 40 of these species are lost or it was impossible to prove the type character of the material still available. At least a part of the type material of the following 20 Ratzeburg species is preserved with more or less probability: Chelonus atriceps (no. 1), Bracon hylesini (no. 9), B. middendorjfii (no. 12), B. praecisus (no. 15), B. initiatellus (no. 17), B. palpebrator (no. 18), B. labrator (no. 19), B. sordidator (no. 20), B. laevigatus (no. 22), Spathius radzayanus (no. 26), Microgaster hoplites (no. 32), M. inclusus (no. 35), M. terebrator (no. 37), M. ater (no. 40), Perilitus rugator (no. 47), P. brevicornis (no. 49), Opius rubrieeps (no. 52), Rogas limbator (no. 55), Cosmophorus klugii (no. 60) and Bracon multiarticulatus (no. 61). One specimen of Spathius exannulatus (no. 23), although it is one of the original series, cannot be regarded as a type because it belongs to another species.